CoDaaS : an experimental cloud-centric content delivery platform for user-generated contents - Jin, Yichao (2013)
User-generated content (UGC) is emerging as one of the dominate forms in global media industry. However, the efficient delivery of UGC faces with massive technical challenges due to its long-tail nature. Content delivery networks (CDN) based systems are considered as the potential solutions to deliver UGC. But none of the existing CDN based solutions can support all the required features in UGC delivery. This paper proposes content-delivery-as-a-service (CoDaaS), an innovative idea to enable on-demand virtual content delivery service (vCDS) overlays for UGC providers to deliver their contents to a group of designated consumers. The proposed CoDaaS solution is built on a hybrid media cloud, and offers elastic private virtual content delivery service with an agreed Quality of Service (QoS) to UGC providers. In this paper, we also implement a simulation to CoDaaS. The preliminary results validate all the required features for UGC delivery and verify its comparative performance advantages. We are working on optimizing the system performance with different algorithms (e.g., collaborative caching, context-aware streaming, etc), and ultimately characterizing the fundamental trade-off between the cost and the quality-of-service in UGC delivery.